The role of CD74 in cardiovascular disease - Li, Qiu-Lin; Tang, Jing; Zhao, Ling; Ruze, Amanguli; Shan, Xue-Feng; Gao, Xiao-Ming (Frontiers in Cardiovascular Medicine, 2023)
Leukocyte differentiation antigen 74 (CD74), also known as invariant chain, is a molecular chaperone of major histocompatibility complex class II (MHC II) molecules involved in antigen presentation. CD74 has recently been shown to be a receptor for the macrophage migration inhibitory factor family proteins (MIF/MIF2). Many studies have revealed that CD74 plays an important role in cardiovascular disease. In this review, we summarize the structure and main functions of CD74 and then focus on the recent research progress on the role of CD74 in cardiovascular diseases. In addition, we also discuss potential treatment strategies that target CD74. Our systematic review of the role of CD74 in cardiovascular disease will fill some knowledge gaps in the field.